Absolute electromagnetic transition rates in semi-magic N = 50 and 126 isotones as a test for (π9/2)n single particle calculations - Jolie Jan; Karayonchev Vasil; Ley Mario; Blazhev Andrey; Esmaylzadeh Arwin; Knafla Lukas; Harter Andreas; Régis Jean-Marc; Kocheva Diana; Rainovski Georgi; Van Isacker Piet (EPJ Web of Conferences)
Assuming a seniority-conserving interaction, single-j calculations for (j)n configurations with n = 1,..,2j+1 can be performed using a semi-empirical approach, provided that the energies and absolute electromagnetic transition rates are known for the two-particle (hole) nucleus. Using those and the coefficients of fractional parentage, all needed matrix elements for the (j)n configurations can be predicted. At the Cologne Tandem Accelerator of the Institute for Nuclear Physics these relations were tested by measuring lifetimes of excited states in (π9/2)n isotones with N = 50 and N = 126 over the last years. The studies started in the two-proton nucleus 210Po where the abnormal B(E2:21+ → 01+) value was remeasured, providing important input for the other N = 126 configurations. Then lifetimes of excited states in 211At were measured using the electronic γ-γ fast timing technique, the Recoil Distance Doppler Shift (RDDS) method, and the Doppler Shift Attenuation (DSA) method. Very good agreement with the analytical single -j calculation is obtained. For N = 50 isotones, we recently started by measuring the previously unknown B(E2:41+→ 21+) value in 92Mo needed for the prediction of other N = 50 isotones. We also report on experiments on 93Tc and 94Ru.